Molecular diagnostics in South Africa and challenges in the establishment of a molecular laboratory in developing countries - Ashika Singh-Moodley; Husna Ismail; Olga Perovic (Journal of Infection in Developing Countries)
The laboratory plays a significant role in public health surveillance, outbreak investigation and infection prevention and control strategies. Microbiology laboratories are moving towards incorporating molecular biology techniques for the surveillance and identification of pathogens causing infectious diseases as well as the genotypic characterisation of these organisms. These methods are accurate, rapid, reliable, and provide a wealth of information that are not available using conventional phenotypic methods. However, establishing such a laboratory can be challenging in developing countries due to poor infrastructure, the lack of funding and the required expertise. This manuscript discusses the essential issues that need to be addressed when establishing a molecular microbiology laboratory and the usefulness of molecular techniques in public health surveillance and outbreaks in developing countries. Molecular data on South African findings obtained from surveillance and outbreak studies are also presented in this manuscript.